The Relationship Between Qana'ah and Psychological Welfare of Parents Who Have Children with Special Needs in Pekanbaru City - Yolla Riska Andriani (Journal Research of Social Science, Economics, and Management, 2022)
Psychological well-being is a condition when individuals can accept their own shortcomings, have a purpose in life, can build good relationships with others, are independent from social pressures, and can control their environment. The purpose of this study was to determine the relationship between Sana'a and the psychological well-being of parents who have children with special needs. The sampling technique in this study used a cluster sampling technique. The number of samples in this study were 130 samples at the Kasih Ibu Special School. The number of samples taken was 60 samples, at SLB Kinasih as many as 30 samples, at SLB Panam Mulia as many as 22 samples, and SLB Al-Faqih as many as 18 samples. The data analysis technique used Pearson's product-moment correlation technique. Hypothesis testing in this study used Pearson's product-moment correlation analysis technique to determine the form of the relationship between qana'ah trait variables on psychological well-being. The results of Pearson's correlation analysis for psychological well-being (Y) and qana'ah (X) characteristics with a sample of 150 obtained a (r) value of 0.711 and a Sig (2-tailed) value. ) or p 0.000 (p < 0.05). meaning 'the hypothesis is accepted' means that there is a positive and significant relationship between the nature of qana'ah with psychological well-being. The correlation value of 0.711 is in the interval 0.60 – 0.80, meaning that between the qana'ah variable and the psychological welfare variable there is a strong correlation (Siregar, 2014). The resulting positive correlation shows the higher the qana'ah, the higher the psychological well-being. And vice versa, the lower the qana'ah, the lower the psychological well-being. In this study, qana'ah has an effective contribution of 50.5% and the rest is influenced by other factors of 49.5%.